IMPLEMENTASI PENGGUNAAN MODEL TGT DAN GI UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VIII B SMPN I PARINGIN PADA KONSEP SISTEM PENCERNAAN MAKANAN - Juni Angkowati (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2014)
Abstract. Implementation of TGT model and GI on food in the digestive system concept B class VIII SMPN I Paringin expected to increase the activity and student learning outcomes. In addition, this research purpose to increase the activity of teachers and students' response to the learning model of TGT and GI. This type of research is a kind of action research Classes (Classroom Action Research). The study consisted of two cycles, and each cycle consisted of two meetings with the planning, implementation, observation, and reflection. The subjects were students of class VIII B SMPN 1 Paringin totaling 20 people, 9 men and 11 women. Results showed increased activity of teachers of the first cycle of 94% to 96.25% in the second cycle in the excellent category, the learning activities of students has increased in the first cycle TGT learning model by 77% and the learning model GI of 75.84% while in the second cycle TGT learning model by 95% and GI learning model by 96%. Learning outcomes of students also increased from the action, which is an average result of learning the first cycle of 68.25%, and in the second cycle of 98.95% with a classical KKM 76. While the expected 85% of students completed can also be achieved, it this can be seen in the first cycle of 70% and the second cycle has reached 90%. Response / feedback class VIII B SMPN 1 Paringin responded positively to the learning model of TGT and GI.Keywords: Activities Learning, Learning Outcomes, Learning Model, TGT, GI.